Preparation and evaluation of new reference materials for naturally occurring radioactive materials (NORM): Zirconium silicate, bauxite, and phosphogypsum. (February 2021) - Lee, JuHyun; Kim, Yong-Jae; Chae, Jung-Seok; Oh, Jung Suk; Kwon, EunHee; Lim, Jong-Myoung; Lee, Hoon; Han, Jeong Hee; Pham, Mai Khanh; Nour, Svetlana; La Rosa, Jerome; Gaca, Pawel; et al.
Abstract: New reference materials (RMs), zirconium silicate, bauxite and phosphogypsum, were produced and characterized according to an ISO guide. The homogeneity of the three RMs was evaluated using X-ray fluorescence (XRF), and characterizations of the three candidate materials were performed through a collaborative study with nine expert radioanalytical laboratories. The assigned radionuclides are 230 Th, 232 Th, 234 U, 235 U, and 238 U for zirconium silicate; 230 Th, 232 Th, 234 U, and 238 U for bauxite; and 226 Ra, 230 Th, 234 U, and 238 U for phosphogypsum. Highlights: Three new reference materials for naturally occurring radioactive materials (NORM) were produced and characterized. The characterization of three reference materials was performed according to an ISO Guide 35. The reference values of the three candidate materials were performed through a collaborative study. Aimed at QA/QC for the validation of NORM analytical methods.